Contribution to subfamily Rhaphidophorinae Walker, 1869 (Orthoptera: Rhaphidophoridae) in China IX: New additions of Rhaphidophora from Yunnan and Xizang - Qin, Yanting; Bian, Xun (Zootaxa, 2024)
This paper describes three new species of Rhaphidophora from Yunnan and Xizang, China and the female sex of Rhaphidophora heterodentis Shen, Wang & He, 2024. All the specimens are deposited in Guangxi Normal University.